Perancangan Aplikasi Pengelolaan Aset Barang Inventaris SDN Makasar 05 Pagi Jakarta Timur - Muhamad Nur Witama (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2019)
Information technology which is engaged in asset management or asset management information systems is one system that is often used by companies including schools. SDN Makasar 05 Pagi one of the schools that has not used a computerized system, one of which is the management of goods assets, making it difficult for officers to provide complete and accurate information. The purpose of this study is to design an asset data application system and asset data report using java programming language and grounded research methods. The results of the system built can facilitate the process of data collection so that it is easier to find the data needed and can help the performance of administrative officers so that it is more effective and efficient.